Enriched Environment Promotes Adult Hippocampal Neurogenesis through FGFRs - Grońska-Pęski, Marta (J Neurosci, 2021)
The addition of new neurons to existing neural circuits in the adult brain remains of great interest to neurobiology because of its therapeutic implications. The premier model for studying this process has been the hippocampal dentate gyrus in mice, where new neurons are added to mature circuits during adulthood. Notably, external factors such as an enriched environment (EE) and exercise markedly increase hippocampal neurogenesis. Here, we demonstrate that EE acts by increasing fibroblast growth factor receptor (FGFR) function autonomously within neurogenic cells to expand their numbers in adult male and female mice. FGFRs activated by EE signal through their mediators, FGFR substrate (FRS), to induce stem cell proliferation, and through FRS and phospholipase Cγ to increase the number of adult-born neurons, providing a mechanism for how EE promotes adult neurogenesis. SIGNIFICANCE STATEMENT How the environment we live in affects cognition remains poorly understood. In the current study, we explore the mechanism underlying the effects of an enriched environment on the production of new neurons in the adult hippocampal dentate gyrus, a brain area integral in forming new memories. A mechanism is provided for how neural precursor cells in the adult mammalian dentate gyrus respond to an enriched environment to increase their neurogenic output. Namely, an enriched environment acts on stem and progenitor cells by activating fibroblast growth factor receptor signaling through phospholipase Cγ and FGF receptor substrate proteins to expand the pool of precursor cells.